2005
DOI: 10.1021/ja0554357
|View full text |Cite
|
Sign up to set email alerts
|

Living Ring-Opening Polymerization of N-Sulfonylaziridines:  Synthesis of High Molecular Weight Linear Polyamines

Abstract: Sulfonylaziridines have been identified as excellent monomers for living ring-opening polymerization initiated by nucleophilic sulfonylamides. The resulting polymers exhibit low polydispersities and controllable molecular weights. The enantiopurity of the monomer plays a key role: racemic samples yield soluble polymers of target molecular weights, while enantiopure samples produce insoluble polymers with molecular weights significantly below theoretical values. Dynamic light scattering and kinetics of polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 10 publications
7
133
0
Order By: Relevance
“…To this end, we were inspired by observations made during the course of our investigation of gold-catalyzed alkene cyclopropanation using propargyl esters as carbene precursors. 14 During these studies we noted that the cis - trans diastereomeric ratio of the cyclopropanation product depended on the steric properties of the phosphine ligand on gold. The observed selectivity for the cis isomer was rationalized by a concerted cyclopropanation model, involving the intermediacy of a cationic gold(I)-carbene intermediate, whose bonding and reactivity have subsequently been investigated by our research group and others (Scheme 2).…”
Section: Enantioselective Reactions Catalyzed By Bis(phosphine)digoldmentioning
confidence: 99%
“…To this end, we were inspired by observations made during the course of our investigation of gold-catalyzed alkene cyclopropanation using propargyl esters as carbene precursors. 14 During these studies we noted that the cis - trans diastereomeric ratio of the cyclopropanation product depended on the steric properties of the phosphine ligand on gold. The observed selectivity for the cis isomer was rationalized by a concerted cyclopropanation model, involving the intermediacy of a cationic gold(I)-carbene intermediate, whose bonding and reactivity have subsequently been investigated by our research group and others (Scheme 2).…”
Section: Enantioselective Reactions Catalyzed By Bis(phosphine)digoldmentioning
confidence: 99%
“…Replacement by an electron‐withdrawing group facilitates this, while simultaneously activating the ring. In one single work it has been reported that tosylation or mesylation of aziridines enables anionic ring‐opening polymerization …”
Section: Introductionmentioning
confidence: 99%
“…Deuterated solvents were purchased from Deutero GmbH. N ‐benzyl methanesulfonamide (BnNHMs), 2‐methyl‐ N ‐tosylaziridine (TsMAz), and 2‐methyl‐ N ‐mesylaziridine (MsMAz) were synthesized according to already published procedures and dried by azeotropic distillation from benzene to remove traces of water . 2‐Methylaziridine was distilled from CaH 2 prior use.…”
Section: Methodsmentioning
confidence: 99%